Penguatan Manajemen Pemasaran UMKM Rokita Bakery di Jl.Lamper Semarang, melalui Strategi Digital Marketing dan Branding Produk - Hendri Rasminto; Edy Siswanto; Nindi Anggi Wardani; Bagus Sudirman; Haris Ihsanil Huda; Ahmad Ashifuddin Aqham (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
The rapid development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to strengthen their marketing capabilities through digital transformation. This community service program aimed to enhance the marketing management of Rokita Bakery MSME located on Lamper Street, Semarang, through the implementation of digital marketing and product branding strategies. The program employed a participatory approach consisting of needs assessment, training, hands-on practice, mentoring, and evaluation activities. The training materials focused on digital marketing concepts, social media optimization, product branding development, product photography techniques, and the creation of attractive promotional content. The results showed an improvement in participants’ understanding and skills in implementing digital marketing and branding strategies, as reflected in a more consistent brand identity, improved product presentation, and increased ability to produce engaging promotional materials. This program is expected to strengthen the competitiveness of Rokita Bakery MSME, expand market access, increase consumer engagement, and support sustainable business growth through effective utilization of digital platforms in the digital era